2000
DOI: 10.1001/jama.284.6.723
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Youth Cigarette Use and Intentions Following Implementation of a Tobacco Control Program

Abstract: Progress toward reduction of youth tobacco use was observed in each of the 2 years of Florida's Pilot Program on Tobacco Control. Our results suggest that a comprehensive statewide program can be effective in preventing and reducing youth tobacco use. JAMA. 2000;284:723-728

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 5 publications
1
121
0
Order By: Relevance
“…[15][16][17][18][19] The most crucial objection was that the focus group responses were self-reported reactions to exposure to various ads, rather than actual behavioral outcomes in response to real-life exposure over time. 17 The behavioral results from the Florida countermarketing campaign support Goldman and Glantz's conclusions, 20 as do the reported results from California, where consumer awareness of industry practices also figured prominently in the ad campaign that proved effective. 7 The youth-inspired "truth" Campaign was developed not to goad the tobacco industry but rather to reduce youth smoking, and it is likely to succeed.…”
Section: Response To the Campaignsupporting
confidence: 58%
See 1 more Smart Citation
“…[15][16][17][18][19] The most crucial objection was that the focus group responses were self-reported reactions to exposure to various ads, rather than actual behavioral outcomes in response to real-life exposure over time. 17 The behavioral results from the Florida countermarketing campaign support Goldman and Glantz's conclusions, 20 as do the reported results from California, where consumer awareness of industry practices also figured prominently in the ad campaign that proved effective. 7 The youth-inspired "truth" Campaign was developed not to goad the tobacco industry but rather to reduce youth smoking, and it is likely to succeed.…”
Section: Response To the Campaignsupporting
confidence: 58%
“…6,7 A similar campaign in Florida was associated with a decline in tobacco use of 40% among middle school students and 18% among high school students. 8 Although the decline was partially attributable to other aspects of the Florida Tobacco Control Program and to price increases, most observers believe the countermarketing campaign played a significant part.…”
Section: Campaigns To Reduce Tobacco Usementioning
confidence: 99%
“…52 The tobacco industry has vigorously fought efforts to alter the image of their product through political campaign contributions, lobbying, litigation, co-opting media to promote "reasonable doubt" about harms, using funds and influence to bias scientific research and communication, and diverting of resources from effective programs to ineffective ones. 53 Smoking rates have decreased in response to legislative and regulatory interventions including increasing taxes on tobacco products, restricting youth access to tobacco products, restriction of tobacco advertising, and clean air laws (including in workplaces, bars, restaurants, schools, child care facilities, parks, entertainment venues, and other public facilities) as well as interventions that changed the image of tobacco (such as release of the first Surgeon General's report, 54 the Truth campaign, 55,56 and mass-media and antismoking campaigns). 3 Effective public policy measures are essential to control the tobacco epidemic and protect children's health.…”
Section: Figurementioning
confidence: 99%
“…12 More recently, The Master Settlement Agreement between the states and the tobacco industry has since allowed states to develop tobacco use prevention and reduction programs. 13 Even after intensive enforcement of local youth tobacco access laws, however, some data have shown that teen smoking rates remained unchanged.…”
Section: Introductionmentioning
confidence: 99%